Ptiliola flammifera (Młynarski) reinstated as a species distinct from P. kunzei (Heer) (Coleoptera: Ptiliidae) - Vorst, Oscar (Zootaxa, 2007)
Ptiliola flammifera (Młynarski) is recognised as a species distinct from P. kunzei (Heer). Apart from differences in the structure of the aedeagus, both species can be separated by the pronotal surface and the apical fringe of the elytra. The male of P. flammifera carries a distinct tuft of hairs on the metaventrite, absent in P. kunzei. Currently, P. flammifera is only known from Poland and the Netherlands. A key for the identification of all three Palaearctic Ptiliola species is presented. A lectotype is designated for Trichopteryx kunzei Heer, 1841.